Answer :

Given, n(A–B) = 30, n(A ∪ B) = 180.

It can be concluded that,

(A ∪ B) = (A–B) + B

∴ n(A ∪ B) = n(A–B) + n(B)

180 = 30 + n(B)

n(B) = 180 – 30 = 150.

Hence, n(B) = 150.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Master the Art of Writing Chemical Formulae42 mins

Master Mole Concept in 45 Minutes48 mins

Law of Gravitation40 mins

Combinations of Solids43 mins

Quick Recap of Cell62 mins

Newton's Second Law46 mins

Final Phase & Legacy of the Revolution43 mins

Variation in g with Rotation of Earth42 mins

Circles- All kinds of Questions36 mins

Surface Area and Volume of solids Revision43 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

i. If A = Φ, Tamilnadu Board Math Term-I

Find the number oTamilnadu Board Math Term-I

Write down the poTamilnadu Board Math Term-I

If n(X) = m, n(Y)Tamilnadu Board Math Term-I

The number of eleTamilnadu Board Math Term-I

Let A and B be twTamilnadu Board Math Term-I

If n[P(A)] = 1, wTamilnadu Board Math Term-I

If n(A ∩</sTamilnadu Board Math Term-I